Building Adaptive Leadership Models in the Digital Age: A Conceptual Study - Rukhayati Rukhayati; Awaluddin Awaluddin; Haris Abd Kadir (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The development of digital technology has fundamentally changed organizational structures, processes, and dynamics. In this context, leaders are required to have high adaptability to fast, complex, and uncertain environmental changes. This article aims to examine the concept of adaptive leadership in facing the challenges of the digital age, as well as to develop a conceptual model that can be the basis for the development of future leadership theories and practices. This study uses a narrative literature review approach by analyzing various literature related to adaptive leadership theory, digital leadership, and organizational transformation. The results of the study show that adaptive leadership in the digital era includes three main dimensions, namely digital capabilities, behavioral flexibility, and strategic collaboration. These three dimensions are the foundation for building leaders who are resilient, innovative, and responsive to technological dynamics. This study contributes to leadership theory by proposing a conceptual model of adaptive leadership tailored for the digital era, highlighting digital capabilities, behavioral flexibility, and strategic collaboration. It provides guidance for organizations to develop leaders who are resilient, innovative, and responsive to technological changes.